(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
As talks of globalization and the learning based economy become progressively persuasive in both policy-production and in open discussions about education, employability and national aggressiveness – the choice of language in the study hall takes on a key significance. The paper utilizes a critical pragmatist Cultural Political Economy focal point to investigate the utilization of English as a medium of instruction (EMI) at tertiary level. The dialog expands on existing theoretical framings and on observational investigation into the language–globalization nexus, just as on language-in-education policy and practice. Thusly, the paper tries to build up a theoretical record of historically and spatially arranged socio-political and financial processes that have favored the utilization of EMI in the area. The attention here is on the persuasive connection between domineering imaginaries (semiosis) and material practices in connection to the worth appended to specific semantic assets, where worth is comprehended in both economic and emblematic terms, and how this is regularly attached to neoliberalism and talks of competiveness.